FINANCIAL MANAGEMENT AT THE REGIONAL LEVEL - DONCHAK, L.; SHKVARUK, D. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article substantiates the importance of such concepts as "management", "financial management", which are the main basis for the effective functioning of the financial sphere of the country. Financial management in the state is carried out through a system of state bodies and institutions using forms and methods of organizing management activities. As for the essence of financial management, we can say that it is a certain system of tools, methods, actions, mechanisms that ensure the effective use of financial resources to obtain the desired result. With the conditions of decentralization of public administration, the competencies of local authorities in financial management are somewhat broader, so the article needs to be clarified. These functions are: financial control over budget expenditures and revenues of the region; performance of powers delegated by central authorities; fiscal stimulation of the region’s economic development; ensuring accountability and control over the territorial community and others. Financial management at the regional level is an important and integral part of all economic systems in the region. Based on the analyzed data, the main stages of financial management of the region, such as financial planning, strategic management, operational management and financial control. One of the main elements of financial management is financial control. Control passes through all stages of management activities, in order to compare the actual results with the planned ones. On the one hand, financial control is control over the formation, distribution and use of financial resources, and on the other hand, the final control, ie control at each stage of financial management. The mechanism of financing the region is also proposed, and the close interrelation of the main elements of financial management at the regional level is proved, ie they act as functions that ensure effective functioning and management of the entire financial system of the region and cannot function as separate systems.